Contribuições do design estratégico para o fomento de inovações no polo moveleiro da Serra Gaúcha - Bischoff, Vanessa Neto (Universidade do Vale do Rio dos Sinos, 2010)
This paper presents the research which aimed at identifying contributions of strategic design for the stimulation of innovation at the wooden - rectilinear, in series – home furniture segment of Rio Grande do Sul State's furniture sector. The study was based on the analysis of companies located at the Rio Grande do Sul Sierra's furniture pole belonging to this segment. Investigation was outlined by a case study, qualitative research. From this case study, existing gaps were identified in the studied segment concerning the stimulus context and the development of innovations through design. As for the suggestions for improvement on the identified gaps, contributions point directly to the use of strategic design. Aiming at promoting innovation development, this study presented, through strategic design, relevant suggestions and subsidies for application on the Rio Grande to Sul State's furniture sector.
Keywords: Inovação; Design; Design estratégico; Desenvolvimento de novos produtos; Setor moveleiro; Innovation; Strategic design; Development of new products; Furniture sector; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial